Clay minerals, iron/aluminum oxides, and their contribution to phosphate sorption in soils — A myth revisited - Gerard, Frederic (Geoderma, 2016)
There is a general consensus that adsorption/desorption (i.e. sorption) is the major process controlling dissolved PO4. However, many uncertainties exist with respect to PO4 sorption capacity and properties of clay minerals as compared to Fe/Al oxides. I reviewed experimental studies performed over a time period of 70years in an attempt to rationalize this knowledge. I found that the binding capacity of clay minerals may be close to or even higher than that of Fe/Al oxides, depending on the specific surface area of these soil constituents. I also found that the pH-dependency of PO4 sorption on clay minerals can differ greatly from that on Fe/Al oxides depending on PO4 loading. Surface reactions occurring at structural Al sites of clay minerals appeared to consistently control sorption at low PO4 concentrations. The analysis indicates that different sorption sites such as structural Fe sites and/or other processes such as the penetration of PO4 into amorphous regions of the mineral are more effective at controlling PO4 sorption at high concentrations. The implications of these findings in soil and rhizosphere are discussed. The possible contributions of kaolinite and goethite to PO4 sorption in a clayed ferralitic soil were estimated. Results suggest that in most soils clay minerals should be considered per se as important PO4-binding constituents, possibly outcompeting Fe/Al oxides. [Display omitted] •Clay minerals can bind substantial phosphate with respect to goethite and gibbsite.•Clay minerals and metal oxides can exhibit different sorption envelopes.•The same sorption envelopes are observed at elevated phosphate loading.•Phosphate sorption seems to occur onto two types of structural sites.